Summer air temperatures in Ljubljana (Slovenia) and Olomouc (Czech Republic) in the period 1961-2000 - Jurek, Martin (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2005)
The paper analyses daily maximum temperatures in Ljubljana, Slovenia, and Olomouc, Czech Republic, in the summer months 1961-2000 in order to validate the assumption on global warming affecting climate in Central Europe. Data on maximum temperatures were processed to reveal trends in temperature variability as well as in the frequency of summer days (days with maximum temperature 25.0°C or higher) and tropical days (tmax 30.0°C or higher).
Keywords: climatology; klimatologija; zrak; temperatura; Ljubljana; Olomouc